RBM20-mutations induce disturbed splicing of calcium relevant genes and guides clinically therapy in different cardiomyopathies. (14th October 2021) - Rebs, S; Sedaghat-Hamedani, F; Kayvanpour, E; Huebscher, D; Wagdi, A; Hasenfuss, G; Meder, B; Streckfuss-Boemeke, K
Abstract: Background: Mutations in the splice factor RBM20 account for ∼3% of genetic cardiomyopathies. Mutations at position R634 in the hotspot RS-domain were found to cause dilative cardiomyopathy (DCM) (R634W) or left ventricular non-compaction cardiomyopathy (LVNC) (R634L), but the pathophysiological mechanisms that govern the heterogeneity in phenotype presentation remain unknown. Purpose: We aimed here to identify the molecular events caused by the distinct RBM20 mutations from DCM and LVNC patients using a patient-specific induced stem cell model (iPSC) and test if the currently clinically used β-blockers (Metroprolol) are suitable for different RBM20-dependent cardiomyopathies. Methods: We generated iPSC-cardiomyocytes of 2 DCM- and 2 LVNC-patients harboring the RBM20-mutations R634W (DCM) or R634L (LVNC). We investigated alternative splicing, sarcomeric regularity, cAMP-level, kinase-specific phosphorylation of Ca2+ players and Ca2+ handling. To investigate the impact of the genetic background, isogenic rescue lines were generated by CRISPR/Cas9. Different clinical drugs as Metoprolol and Verapamil were used to analyze the pharmacological improvement in vitro. Results: We investigated the splicing pattern of the 2 RBM20 mutations in DCM and LVNC iPSC-CMs and observed common isoform changes in titin and a 24bp-insertion in the gene RYR2. The Ca2+ handling gene triadin is misspliced in LVNC-CMs, whereas the structural gene LDB3 is misspliced in DCM-CMs. As a possible consequence of splice defects in sarcomeric genes, both DCM and LVNC-CMs exhibited an irregular sarcomeric structure. The Ca2+ handling gene CAMK2δ was predominantly misspliced in LVNC-CMs leading to CAMK2δ-dependent hyperphosphorylation of its target PLN-Thr17 and subsequently to shortened Ca2+ elimination time and weakened response to β-adrenergic stimulation. By contrast, DCM-CMs exhibited increased Ca2+ sparks and decreased systolic and diastolic Ca2+ levels. RBM20 expression itself was decreased in LVNC-CMs, but not in DCM-CMs. This highlights that 2 distinct RBM20 mutations can lead to different pathological Ca2+ phenotypes. Isogenic CRISPR/Cas9 repair of both RBM20 mutations in LVNC and DCM demonstrated a rescue in gene missplicing, sarcomeric regularity and the Ca2+ handling aberrations and underscored the causative nature of the 2 mutations and their diverging effects. Ca2+ channel blockage with Verapamil showed a significant improvement of some of the LVNC disease characteristics compared to commonly clinically used β-blocker Metoprolol and underpins the potential clinical use of this drug in patients with LVNC. Conclusion: We show the first iPSC-model of splice-defect associated RBM20-dependent LVNC and DCM. In summary, our results suggest that the molecular aberrations in alternative splicing differ depending on the distinct mutation in RBM20 and lead to shared and differential pathologies. Verapamil could be a good candidate in the treatment of RBM20-dependent LVNC. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Bunderministerium für Bildung und Forschung BMBFGerman Center for Cardiovascular Research DZHK